2010
DOI: 10.1136/jme.2009.033100
|View full text |Cite
|
Sign up to set email alerts
|

Collection, storage and use of blood samples for future research: views of Egyptian patients expressed in a cross-sectional survey

Abstract: This study shows that many individuals do not favour the donation of a blood sample for future research. Of those who do approve of such future research, many favour a consent model that includes an option restricting the future research to the illness being studied. Also, many Egyptians were hesitant to have their blood samples donated for genetic research or exported out of the Arab region to the USA and European countries. Further qualitative research should be performed to determine the underlying reasons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
64
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(75 citation statements)
references
References 29 publications
(24 reference statements)
8
64
1
2
Order By: Relevance
“…However, the finding that a large proportion of the public do not want their HBSs used for research outside the UK is intriguing. Our qualitative data show that concerns exist around regulation and commodification of HBSs, findings supported elsewhere in the literature 40 41. To address these concerns, potential donors should be provided with information related to the specific issues that relate to those countries where HBSs are likely to be sent.…”
Section: Discussionsupporting
confidence: 87%
“…However, the finding that a large proportion of the public do not want their HBSs used for research outside the UK is intriguing. Our qualitative data show that concerns exist around regulation and commodification of HBSs, findings supported elsewhere in the literature 40 41. To address these concerns, potential donors should be provided with information related to the specific issues that relate to those countries where HBSs are likely to be sent.…”
Section: Discussionsupporting
confidence: 87%
“…Studies from developing countries have shown that RECs face challenges that include lack of member diversity, inadequate training of members, scarcity of human and capital resources, and absence of national regulations (Abou-Zeid, 2010; El-Dessouky et al, 2011; Kandeel et al, 2011; Lakshmi, 2012; Office for Human Research Protections [OHRP], 2010). Similar findings have also been shown for RECs in Egypt, where more than 40 RECs have registered with the Office for Human Research Protections (OHRP, 2010).…”
mentioning
confidence: 99%
“…Of these, 7 studies defined one criterion such as minimum age or language spoken, and the remaining 33 studies defined two or more criteria, such as ‘adult Egyptian patients', excluding those ‘who were critically ill or with diminished decisional capacity' [37]. …”
Section: Resultsmentioning
confidence: 99%